Individual differences in complex grammar acquisition: causes and consequences - Svirko, E (2011)
A longitudinal study lasting 3.5 years was conducted to investigate complex grammar development, focusing on acquisition of the passive and type 3 conditionals, and its relationship with a number of domain-general, domain-specific and environmental factors. 128 children (M = 5 years 10 months) were tested at the beginning and towards the end of each school year starting from Year 1. The administered measures included established tests of fluid intelligence, short-term and working memory, seriation, grammar, vocabulary, literacy and arithmetic, plus newly-developed tests of passive and conditional sentence acquisition, and arithmetic word problem solving. It was demonstrated that grammar acquisition is not complete even when children start Year 4 of primary school (M = 8 years 7 months), when the current study was completed. At that time, 32% of children have not acquired type 3 conditionals and 89% showed no understanding of centre-embedded sentences. However, only 3% showed no passive sentence acquisition. Fluid intelligence, verbal STM and WM, ability to seriate, vocabulary and parental education level were all found to contribute to individual differences in complex grammar acquisition, independently of age differences and, where relevant, independently of non-verbal ability. There were differences between the passives and the conditionals in their relationship to these variables. Complex grammar development was found to be a significant predictor of reading comprehension, spelling and arithmetic performance, independently of age, non-verbal ability, verbal STM and WM. The findings demonstrate the inter-relatedness of higher cognitive functions, particularly domain-general with domain-specific ones. Modularity in its strictest sense (informational encapsulation, functional isolation) is not present in normally developing brains. Educational applications of the results are discussed.